2019
DOI: 10.1007/s10549-019-05380-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-targeted kinase inhibition alleviates mTOR inhibitor resistance in triple-negative breast cancer

Abstract: Purpose Owing to its genetic heterogeneity and acquired resistance, triple-negative breast cancer (TNBC) is not responsive to single-targeted therapy, causing disproportional cancer-related death worldwide. Combined targeted therapy strategies to block interactive oncogenic signaling networks are being explored for effective treatment of the refractory TNBC subtype. Methods A broad kinase inhibitor screen was applied to profile the proliferative responses of TNBC cells, revealing resistance of TNBC cells to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…Targeting therapy of solid tumors represents a great challenge because of heterogeneity of tumor-associated antigen expression. Combination therapy, targeting two (or more) different receptors on a tumor cell has gained considerable attention in the field of oncology in recent years, with numerous studies demonstrating its significant advantage over monotherapies [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting therapy of solid tumors represents a great challenge because of heterogeneity of tumor-associated antigen expression. Combination therapy, targeting two (or more) different receptors on a tumor cell has gained considerable attention in the field of oncology in recent years, with numerous studies demonstrating its significant advantage over monotherapies [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The increased expression of the phosphorylate-type AKT, that is the activation of AKT signaling, is observed in the osteosarcoma cells. 30 It has been reported that the AKT-related signaling pathway mediates drug-resistance in various cancers, such as in gastric cancer 31 and in breast cancer, 32 as well as in osteosarcoma cells. 33 In this research, we found that both PMA-differentiated THP1 and macrophagederived exosomes signicantly increased the expression of phosphorylated AKT, and that the AKT inhibitor MK2206 reversed the effect of the macrophage-derived exosomes, indicating that the macrophage-derived exosomes activated the AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies have provided comprehensive insights into the dynamic pharmacogenomic interactions across a wide spectrum of cancer types, most gene-drug associations have primarily relied on single agent analysis. Combination therapy has gained considerable attention in the field of oncology in recent years, with numerous studies demonstrating its significant advantage over monotherapies (3336).…”
Section: Discussionmentioning
confidence: 99%